Christmas night, fair and bright - Stiegemeyer, Julie; Iwai, Melissa (St. Louis, MO : Concordia Pub. House, 2007)
A retelling in rhyme of the story of Jesus from his birth in a cattle stall to the return from Egypt to Nazareth.
Keywords: Jesus Christ -- Nativity -- Juvenile literature; Jesus Christ -- Nativity; Christmas